HARMONIZING IFRS AND AAOIFI STANDARDS: A LEGAL AND ACCOUNTING ANALYSIS FOR CROSS-BORDER ISLAMIC FINANCIAL INSTITUTIONS - Ahmed Al-Mansoori; Ahmed Al-Sabah; Andi Andi (Yayasan Adra Karima Hubbi, 2025)
The increasing globalization of Islamic finance has created an urgent need to harmonize the International Financial Reporting Standards (IFRS) and the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) standards. This study explores the legal and accounting dimensions of convergence between these two frameworks to ensure transparency, comparability, and Shariah compliance in cross-border Islamic financial institutions. The research aims to analyze the conceptual and operational differences between IFRS and AAOIFI, identify areas of conflict in financial reporting practices, and propose a harmonization model that accommodates both international accounting principles and Islamic jurisprudence. A qualitative legal-accounting approach was employed, combining comparative document analysis and expert interviews with Shariah auditors, regulators, and financial accountants across selected jurisdictions. The findings indicate that while IFRS emphasizes fair value and investor orientation, AAOIFI prioritizes justice and ethical accountability rooted in Islamic law. The harmonization process requires adaptive regulatory mechanisms, mutual recognition frameworks, and integrated training for practitioners. The study concludes that convergence is feasible through a hybrid model aligning IFRS transparency with AAOIFI’s Shariah-based ethics, promoting both global standardization and religious authenticity.